The Influence of Work-Life Balance on Employee’s Turnover Intention (Case Study in Head Office Perum BULOG Jakarta - Milla Dwi Afnisya’id; Pramitha Aulia (Fakultas Bisnis, 2022)
This study aims to determine how the level of work-life balance, the level of employee turnover intention, and the effect of work-life balance on the turnover intention of employees at the head office of Perum BULOG Jakarta. The sample in this study as many as 86 employees with a sampling technique that is the probability sampling. In addition, the data analysis techniques used are descriptive analysis, simple linear analysis, classical assumption test, coefficient of determination, and t test using the SPSS version 26 application to process the data. Based on the results of the study, it shows that the level of employee work-life balance is in the high category, the level of employee turnover intention is in the low category, and the results of simple linear regression analysis show that the work-life balance has a significant negative effect on turnover intention.